Peculiarities of Morphofunctional Changes in Brain Structures of Rats of Various Age when Forming the Active Avoidance Behavior Following General Cooling - Nikishkova, I. N. (Problems of Cryobiology and Cryomedicine, 2003)
There have been considered the peculiarities of morphofunctional changes of brain structures in 3- and 6-monts’ rats when training on the model formation for active avoidance behavior (AAB) following a three-fold general moderate cooling.